1986
DOI: 10.3109/15563658608995392
|View full text |Cite
|
Sign up to set email alerts
|

Pilot survey of urinary porphyrins from persons transiently exposed to a pcb transformer fire

Abstract: In rats and humans chronically exposed to large amounts of PCB (polychlorinated biphenyls) and PCDF (polychlorinated dibenzofurans), the urinary excretion of uroporphyrin and coproporphyrin are altered. However, porphyrin excretion in humans after acute transient low level exposure has not been evaluated. Following such an exposure in which bystanders and firefighters were in contact with smoke from a PCB transformer fire, we surveyed 90 self-referred individuals by questionnaire and by determining single 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Brewster (9) has reviewed the usefulness ofmeasuring total urine porphyrins to detect xenobiotic exposures to heavy metals, hormones, drugs, and halogenated aromatic hydrocarbons. These chemicals induce chronic disturbances in hepatic synthesis ofporphyrins (Tible 4) and thus lead to excess porphyrin excretion and skin symptoms in the final stage (107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124).…”
Section: Porphyrinsmentioning
confidence: 99%
“…Brewster (9) has reviewed the usefulness ofmeasuring total urine porphyrins to detect xenobiotic exposures to heavy metals, hormones, drugs, and halogenated aromatic hydrocarbons. These chemicals induce chronic disturbances in hepatic synthesis ofporphyrins (Tible 4) and thus lead to excess porphyrin excretion and skin symptoms in the final stage (107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124).…”
Section: Porphyrinsmentioning
confidence: 99%
“…Similar results have been noted by Stark et a1.28 in their study of men exposed to PCBs from a transformer explosion in Syracuse, N.Y. Seppalainen et al" have found slight and reversible impairment of the peripheral nerves among workers in a Finnish cardboard plant after a capacitor explosion. Osterloh et al 30 have examined urinary porphyrins in 90 persons transiently exposed to a PCB transformer fire, and concluded that excretion levels were unaltered and that they were insensitive measures of exposure.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, uroporphyria developed after the same oil mixture was administered to mice . Likewise, among people poisoned by polychlorinated biphenyls (PCBs) and polybrominated biphenyls (PBBs), disturbances of porphyrin metabolism have been detected by levels and patterns of the porphyrins excreted in urine, but clinical porphyria manifested by cutaneous symptoms of PCT is rare ,,− .…”
Section: Chemical-induced Uroporphyriamentioning
confidence: 99%